Plasma undercarboxylated osteocalcin dynamics with glycemic stress reflects insulin sensitivity and beta-cell function in humans with and without T2DM - Kelly N.Z. Fuller; Erin M. Bohne; Jacob T. Mey; Brian K. Blackburn; Victoria R. Miranda; Krista A. Varady; Kirstie K. Danielson; Jacob M. Haus (Metabolism Open, 2023)
This study aimed to better understand the relationship between bone-related biomarkers and nutrient stress in the context of metabolic health. We investigated plasma osteocalcin (OC) during an oral glucose challenge and experimental hyperinsulinemia in Type 2 diabetes (T2DM) and lean healthy controls (LHC). Older individuals with obesity and T2DM (n = 9) and young LHCs (n = 9) underwent a 75g oral glucose tolerance test (OGTT) and a 40 mU/m2/min hyperinsulinemic-euglycemic clamp. Plasma undercarboxylated OC (ucOC) and total OC were measured at baseline, 60mins, and 120mins of the OGTT and clamp via ELISA. In addition, plasma alkaline phosphatase (ALP), leptin, adiponectin, Vitamin D and insulin were measured and indices of insulin sensitivity and β-cell function were derived. The T2DM group had lower (p<0.05) ucOC and ucOC:total OC ratio than LHC during both the OGTT and clamp. Further, baseline ucOC was positively correlated to indices of β-cell function and negatively correlated to indices of insulin resistance when both groups were combined (all p<0.05). Suppression of OC observed in T2DM may be related to glucose intolerance and insulin resistance. Similarly, our data suggest that the observed phenotypic differences between groups are likely a product of long-term glucose dysregulation rather than acute flux in glucose or insulin.